Establecimiento de un mercado justo de pagos por publicar en acceso abierto - Baiget, Tomí s (Anuario ThinkEPI, 2015)
Reseña del informe: Bjí¶rk, Bo-Christer; Solomon, David J. (2014). Developing an effective market for open access article processing charges. Final report to a consortium of research funders comprising Jisc, Research Libraries UK, Research Councils UK, Wellcome Trust, Austrian Science Fund, Luxembourg National Research Fund and Max Planck Institute for Gravitational Physics. http://goo.gl/k2oeqX